Ethnography: Fundamentals, Opportunities and Complexities - Shrestha, Narayan (Journal of Kathmandu BernHardt College, 2025)
This article examines the issue of defining and understanding ethnography as both a method and a writing practice within the human sciences, highlighting its role in explaining culture its norms, values, traditions, institutions, behaviors, and beliefs through participant observation, interviews, and personal narratives. The main objective is to discuss the scope and importance of ethnography for researchers, emphasizing that ethnographic inquiry requires developing an awareness of lived experiences, complexities, contradictions, and insider perspectives of cultural groups. Methodologically, the paper draws on historical foundations of ethnography, Agar’s conceptualization of the “ethnographic space of possibilities,” and a comparative discussion of different types of ethnographic research, distinguishing between those that align with ethnographic sensibility and those that do not. The findings underscore that ethnography is driven by iterative, recursive, and abductive logic, enabling researchers to uncover both shared and contrasting viewpoints, and conclude that ethnography has significant applications not only in academic contexts but also in broader fields where understanding human experience is essential.